Use of fine‐needle aspirate calcitonin to detect medullary thyroid carcinoma: A systematic review. Issue 1 (19th October 2015) - Trimboli, Pierpaolo; Guidobaldi, Leo; Bongiovanni, Massimo; Crescenzi, Anna; Alevizaki, Maria; Giovanella, Luca
Abstract : Background: The measurement of calcitonin in washout fluids of thyroid nodule aspirate (FNA‐calcitonin) has been reported as accurate to detect medullary thyroid carcinoma (MTC). The results from these studies have been promising and the most updated version of ATA guidelines quoted for the first time that " FNA findings that are inconclusive or suggestive of MTC should have calcitonin measured in the FNA washout fluid ." Here we aimed to systematically review published data on this topic to provide more robust estimates. Research Design and Methods: A comprehensive computer literature search of the medical databases was conducted by searching for the terms "calcitonin" AND "washout." The search was updated until April 2015. Results: Twelve relevant studies, published between 2007 and 2014, were found. Overall, 413 thyroid nodules or neck lymph nodes underwent FNA‐calcitonin, 95 were MTC lesions and 93 (97.9%) of these were correctly detected by this measurement regardless of their cytologic report. Conclusions: The present study shows that the above ATA recommendation is well supported. Almost all MTC lesions are correctly detected by FNA‐calcitonin and this technique should be used to avoid false negative or inconclusive results from cytology. The routine determination of serum calcitonin in patients undergoing FNA should improve the selection of patients at risk for MTC, guiding the use of FNA‐calcitonin in the same FNA sample and providing useful information to the cytopathologist for the morphological assessment and the application of tailored ancillary tests. Diagn. Cytopathol. 2016;44:45–51. © 2015 Wiley Periodicals, Inc.